NDRG1 is expressed in human granulosa cells: An implicative role of NDRG1 in the ovary. (5th January 2022) - Nishigaki, Akemi; Tsubokura, Hiroaki; Ishida, Mitsuaki; Hashimoto, Yoshiko; Yoshida, Aya; Hisamatsu, Yoji; Tsuzuki‐Nakao, Tomoko; Murata, Hiromi; Okada, Hidetaka
Abstract: Purpose: N‐myc downstream‐regulated gene 1 (NDRG1) is expressed in various human tissues and plays a role in regulating cellular proliferation, angiogenesis, and hypoxia sensing. However, the role of NDRG1 in the ovary remains poorly understood. Therefore, we investigated NDRG1 expression and the role of NDRG1 in the human ovary. Methods: Follicular fluid (FF) and luteinized granulosa cells were collected from follicles during oocyte retrieval. KGN cells were cultured with cobalt chloride (CoCl2, a hypoxia‐mimicking agent) and/or echinomycin. mRNA, protein levels and secretion, and localization were assessed by real‐time PCR, Western blotting, ELISA, and immunohistochemical analysis, respectively. KGN cells were also transfected with NDRG1 siRNA for 72 h. Results: NDRG1 protein was expressed in luteinized granulosa cells. NDRG1 concentration was positively correlated with vascular endothelial growth factor (VEGF) and progesterone concentrations in FF. CoCl2 ‐induced hypoxic stress significantly increased NDRG1 and VEGF mRNA and protein and hypoxia‐inducible factor‐1α expression compared with those in the controls. The CoCl2 ‐induced overexpression of NDRG1 and VEGF was suppressed by echinomycin. Transfection with NDRG1 siRNA significantly suppressed the release of progesterone in the culture medium. Conclusions: These results indicate that ovarian NDRG1 may play important roles in follicular development, especially in the early luteinization of pre‐ovulatory follicles.